Comparison of Mat with Elisa and Lat Tests in Detecting Toxoplasma Gondii Antibodies in Human Sera - Mawlood, Hemdad H.; Mero, Wijdan M. S.; Su, Chunlei; Isa, Abdallah M. (Science Journal of University of Zakho, 2017)
The modified agglutination test (MAT) has been widely used for the detection of Toxoplasma gondii infection in numerous animal species. For the standard protocol of MAT test, T. gondii whole cell antigens were produced in the laboratory mice, which was a tedious process. The produced antigen in cell culture was used to assure its capability for MAT test.  For detecting the antibodies of T. gondii in human sera, comparison was made between MAT, enzyme linked immunosorbent assay (ELISA) and latex agglutination test (LAT).  A total of 96 human serum samples were tested. The anti-Toxoplasma IgG antibodies were found in 25.0% (24/96), 20.8% (20/96) and 13.5% (13/96) samples by MAT (cutoff 1:25), ELISA and LAT tests, respectively.  The MAT and ELISA tests matched 95.8% in detection of IgG antibodies, with the positive percent agreement of 100% (20/20) and negative percent agreement of 94.7% (72/76).  For the MAT versus LAT tests, the overall agreement was 88.5% (85/96), with the positive percent agreement of 100% (13/13) and negative percent agreement of 86.7% (72/83). These results suggest a strong correlation between the MAT and ELISA tests in detecting serum IgG to T. gondii in human sera.  In conclusion, T. gondii prepared in cell culture provides an alternative solution to produce antigens for MAT test.
Keywords: Toxoplasma gondii; MAT; LAT; ELISA